2017
DOI: 10.9790/6737-04032830
|View full text |Cite
|
Sign up to set email alerts
|

New performance measure in Cricket

Abstract: Measuring individual performance of players in Cricket is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Many features affect the bowling strength of a team. The essential features are applied to compute the accurate bowling strength of a team in (4).…”
Section: Proposed Methods 1) Region-wise Team 'Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Many features affect the bowling strength of a team. The essential features are applied to compute the accurate bowling strength of a team in (4).…”
Section: Proposed Methods 1) Region-wise Team 'Strengthmentioning
confidence: 99%
“…Research has identified a limited material set of references regarding region-wise and a unified team"s strength; however, a comprehensive review revealed the following. The author developed a new performance measure to quantify the performance of the players [4]. A player scoring runs against a strong bowling lineup or taking wickets against the strong batting lineup deserves more credit.…”
Section: Related Workmentioning
confidence: 99%
“…Lakkaraju and Sethi defined a Saber-metrics style principle to analyze the batting performance in cricket sports [10]. Shah Parag has defined a new measure for the players facing the quality opposition [16]. The author modeled the players' batting and bowling datasets and features to predict an accurate run scored and wickets were taken using classification algorithms [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are limited articles found related to region-wise teams 'ranking; however, a comprehensive review revealed the following. The author developed a new performance measure to quantify the performance of the players [2]. Scoring runs against a strong bowling lineup or taking wickets against the strong batting lineup deserves more credit to a player.…”
Section: Related Workmentioning
confidence: 99%